The DynaDeep observatory – a unique approach to study high-energy subterranean estuaries - Massmann, Gudrun; Abarike, Grace; Amoako, Kojo; Auer, Felix; Badewien, Thomas H.; Berkenbrink, Cordula; Böttcher, Michael Ernst; Brick, Simone; Cordova, Iris Valeria Medina; Cueto, Jairo; Dittmar, Thorsten; Engelen, Bert; et al. (Frontiers in Marine Science, 2023)
Subterranean estuaries are connective zones between inland aquifers and the open sea where terrestrial freshwater and circulating seawater mix and undergo major biogeochemical changes. They are biogeochemical reactors that modify groundwater chemistry prior to discharge into the sea. We propose that subterranean estuaries of high-energy beaches are particularly dynamic environments, where the effect of the dynamic boundary conditions propagates tens of meters into the subsurface, leading to strong spatio-temporal variability of geochemical conditions. We hypothesize that they form a unique habitat with an adapted microbial community unlike other typically more stable subsurface environments. So far, however, studies concerning subterranean estuaries of high-energy beaches have been rare and therefore their functioning, and their importance for coastal ecosystems, as well as for carbon, nutrient and trace element cycling, is little understood. We are addressing this knowledge gap within the interdisciplinary research project DynaDeep by studying the combined effect of surface (hydro- and morphodynamics) on subsurface processes (groundwater flow and transport, biogeochemical reactions, microbiology). A unique subterranean estuary observatory was established on the northern beach of the island of Spiekeroog facing the North Sea, serving as an exemplary high-energy research site and model system. It consists of fixed and permanent infrastructure such as a pole with measuring devices, multi-level groundwater wells and an electrode chain. This forms the base for autonomous measurements, regular repeated sampling, interdisciplinary field campaigns and experimental work, all of which are integrated via mathematical modelling to understand and quantify the functioning of the biogeochemical reactor. First results show that the DynaDeep observatory is collecting the intended spatially and temporally resolved morphological, sedimentological and biogeochemical data. Samples and data are further processed ex-situ and combined with experiments and modelling. Ultimately, DynaDeep aims at elucidating the global relevance of these common but overlooked environments.